Investigation on Mosquitoes Fauna (Diptera: Culicidae) and Probable Vector of West Nile Virus in Lorestan Province, Western Iran - Seyed Hassan Moosa-Kazemi; Yadollah Etemadi; Mohammad Mehdi Sedaghat; Hamid Mokhayeri; Hassan Vatandoost; Mohammad Hassan Kayedi (Tehran University of Medical Sciences, 2022)
Background: Fauna and larval habitat characteristics studies on mosquitoes are important tools to identify the breeding places of the vectors and management of the control strategies. This study was done to provide data on Culicidae fauna, larval habitat characteristics and identifying potential vectors of West Nile virus in Lorestan Province, west of Iran. Methods: Culicidae mosquitoes were collected at three counties and nine site stations from Lorestan Province, west of Iran in 2017. Adult mosquitoes were collected using human and animal bite collection methods, New Jersey and CDC light traps and pit shelters by aspirator. Larva were collected by dipping method. RT-PCR technique was employed for detection of the West Nile virus among mosquito's samples. Results: 4805 mosquitoes were collected from three counties and nine sites in Lorestan Province during June-October 2017, including 4363 adults and 442 larvae. The most abundant species collected from all counties in both adult and larval stages were Culex pipiens (49.10%), Cx. theileri (31.82%), Anopheles maculipennis (11.09%), An. superpictus (2.66%), An. stephensi (2.12%), Cx. perexiguus (1.89%), An. dthali (1.17%) and An. sacharovi (0.15%) respectively. West Nile virus was detected in none of mosquitoes examined. Conclusion: The results of this study revealed that arbovirus vectors such as Cx. pipiens along  with Cx. theileri and Cx. perexiguus are well adapted to a broad range of habitats and different climatic conditions in Lorestan Province. That necessitates further routine surveillance of arboviral infections.